Possible Factors Determining Individual Decisions as Sociopreneurs In The National Strategic Tourism Area of Borobudur - Habibi, Hafidz Nasim; Intan, Ikhtiara Anggitiya; Kusumaningrum, Yunita; Syarifah, Yetty; Fauziyah, Nasywaa; Panjawa, Jihad Lukis (IJBLE Scientific Publications Community Inc., 2025)
As an innovative solution to social issues and a driver of the local economy, sociopreneurship holds crucial relevance in strategic areas such as the national strategic tourism area of Borobudur. This study aims to analyze the determining factors that influence individuals' decisions to become sociopreneurs in the area. Using Utility Theory and Neoclassical Labor Choice Theory, the study applies a quantitative approach with a probit regression model. Primary data were analyzed from 140 respondents (sociopreneurs and non-sociopreneurs) selected through purposive sampling. The main results indicate that age, training, community participation, number of workers, and local resources have a significant positive effect. Conversely, the use of production technology has a negative effect, while capital and formal education factors are not significant. The main conclusion suggests that the decision to become a sociopreneur is driven by a balance of social and economic utility, not simply capital. The implications of this research recommend strengthening policies focused on community-based training and utilization of local resources